All Days 2011
DOI: 10.4043/21716-ms
|View full text |Cite
|
Sign up to set email alerts
|

Perdido Startup: Flow Assurance and Subsea Artificial Lift Performance

Abstract: The Perdido Regional Host is in the ultra-deepwater Gulf of Mexico, and produces from two Lower Tertiary horizons in multiple drill centers; some directly under the host SPAR, and others offset up to 7 miles and in water depths between 7800 and 9600 ft. All of the production is from relatively low-energy reservoirs, and posed considerable productivity challenges. The approaches to managing flow assurance risk and maximizing recoverable volumes were driven by the economically challenged environment in which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…While flowloop investigations weren't reported nearly 20 years after this proposal, two notable field trials were conducted: Tommeliten and Werner Bolley . Alongside these trials, 23 hydrate formation or blockage incidents in transmission lines have been reported in the literature to date. ,− Interestingly, 16 of the 26 total incidences occurred with only condensed water present, that is, water initially dissolved in the gas phase, which precipitates with decreasing temperature, and all cases of complete blockage within this study were associated with transmission lines at or below 12 in. in diameter.…”
Section: Mechanistic Insight Into Hydrate Blockage Formationmentioning
confidence: 71%
“…While flowloop investigations weren't reported nearly 20 years after this proposal, two notable field trials were conducted: Tommeliten and Werner Bolley . Alongside these trials, 23 hydrate formation or blockage incidents in transmission lines have been reported in the literature to date. ,− Interestingly, 16 of the 26 total incidences occurred with only condensed water present, that is, water initially dissolved in the gas phase, which precipitates with decreasing temperature, and all cases of complete blockage within this study were associated with transmission lines at or below 12 in. in diameter.…”
Section: Mechanistic Insight Into Hydrate Blockage Formationmentioning
confidence: 71%
“…• Enablement of increased ultimate volume recovery from low energy reservoir [2,5] • Mitigation of topside water handling capacity constraints [3] • Enablement of heavy oil production [4] • Improved hydrate management [2,5,9] Deployment of subsea processing systems however introduces additional complexity. A careful design and operating strategy has to be carried out to maximize investment rewards, i.e.…”
Section: Introductionmentioning
confidence: 99%